Diagnosis of hemidiaphragm paralysis: refine ultrasound criteria - Boussuges, Alain; Fourdrain, Alex; Leone, Marc; Brioude, Geoffrey; Menard, Amelie; Zieleskiewicz, Laurent; Delliaux, Stephane; Gouitaa, Marion; Dutau, Hervé; Brégeon, Fabienne (Frontiers in Medicine, 2024)
Background: Ultrasound has demonstrated its interest in the analysis of diaphragm function in patients with respiratory failure. The criteria used to diagnose hemidiaphragm paralysis are not well defined. Methods: The aim of this observational retrospective study was to describe the ultrasound findings in 103 patients with diaphragm paralysis, previously diagnosed by conventional methods after various circumstances such as trauma or surgery. The ultrasound study included the recording of excursions of both diaphragmatic domes and the measurement of inspiratory thickening. Results: On paralyzed hemidiaphragm, thickening was less than 20% in all patients during deep inspiration. Thinning was recorded in 53% of cases. In some cases, the recording of the thickening could be difficult. The study of motion during voluntary sniffing reported a paradoxical excursion in all but one patient. During quiet breathing, an absence of movement or a paradoxical displacement was observed. During deep inspiration, a paradoxical motion at the beginning of inspiration followed by a reestablishment of movement in the cranio-caudal direction was seen in 82% of cases. In some patients, there was a lack of movement followed, after an average delay of 0.4sec, by a cranio-caudal excursion. Finally, in 4 patients no displacement was recorded. Evidence of hyperactivity (increased inspiratory thickening and excursion) of contralateral non-paralyzed hemidiaphragm was observed. Conclusion: To accurately detect hemidiaphragm paralysis, it would be interesting to combine the ultrasound study of diaphragm excursion and thickening. The different profiles reported by our study must be known to avoid misinterpretation.